2014
DOI: 10.1002/2013gl058315
|View full text |Cite
|
Sign up to set email alerts
|

Processes controlling Southern Ocean shortwave climate feedbacks in CESM

Abstract: A climate model (Community Earth System Model with the Community Atmosphere Model version 5 (CESM-CAM5)) is used to identify processes controlling Southern Ocean (30-70°S) absorbed shortwave radiation (ASR). In response to 21st century Representative Concentration Pathway 8.5 forcing, both sea ice loss (2.6 W m À2 ) and cloud changes (1.2 W m À2 ) enhance ASR, but their relative importance depends on location and season. Poleward of~55°S, surface albedo reductions and increased cloud liquid water content (LWC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 52 publications
4
72
1
Order By: Relevance
“…We will now discuss how model mixed‐phase behavior appears to influence the cloud feedback. The GCM‐predicted LWP increase with warming that drives the robust negative optical depth cloud feedback at high latitudes (Figure a) [ Gordon and Klein , ; Kay et al ., ; Zelinka et al ., ] has been shown to exhibit a strong dependence on model T5050 [ McCoy et al ., ]. Based on this mechanism we evaluate the dependence of SW cloud feedback on T5050.…”
Section: Resultsmentioning
confidence: 99%
“…We will now discuss how model mixed‐phase behavior appears to influence the cloud feedback. The GCM‐predicted LWP increase with warming that drives the robust negative optical depth cloud feedback at high latitudes (Figure a) [ Gordon and Klein , ; Kay et al ., ; Zelinka et al ., ] has been shown to exhibit a strong dependence on model T5050 [ McCoy et al ., ]. Based on this mechanism we evaluate the dependence of SW cloud feedback on T5050.…”
Section: Resultsmentioning
confidence: 99%
“…The L-only fingerprint F(L) is increasingly apparent in both observational datasets and is incompatible with internal variability. We note, however, that several authors have suggested that cloud shifts may not be trivially related to changes in the jet (Grise and Polvani 2014;Ceppi et al 2014;Kay et al 2014), and further study of the interaction between clouds and the circulation is necessary to understand this response. This is in agreement with previous studies that suggest models fail to capture the observed poleward expansion (Johanson and Fu 2009;Seidel et al 2008).…”
Section: A Observed Poleward Migration Incompatible With Forced Modelsmentioning
confidence: 87%
“…Long-term output of CGCM simulations involving a dynamical sea-ice model may be helpful to further explore the observed relationships with atmospheric variability (Kay et al 2014), because the observational data record of the Antarctic SIC is relatively short and insufficient to conclusively establish a statistical link between sea ice and atmospheric variability. The 150 yr output from the control run (CTR) experiment with the SINTEX-F2 model (Fig.…”
Section: Simulated Sea-ice Variability and Its Impact On Atmospheric mentioning
confidence: 99%